Movement variability and performance of elite alpine skiers descending different slalom course settings - Pérez-Chirinos, C.; Padullés, J. M.; Gavaldà, D.; Trabucchi, M.; Fernández-Valdés, B.; Tuyà Viñas, S.; Moras, G. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: Adaptability to all types of terrain changes, slopes and course settings is a key aspect related to motor control that the best alpine skiers possess. In recent years, several studies have analyzed coordinative aspects of different motor actions by assessing movement variability (MV) through non-linear measurements. From the perspective of human movement, variability is described as the variation that occurs when executing multiple repetitions of the same task. Some of these studies already used an inertial measurement unit (IMU) placed at the athlete to assess MV. So far, no study has measured MV in alpine skiing nor its relationship to performance. Thus, the aims of this study were: a) to evaluate the influence of different slalom course settings on MV and b) to assess the relationship between MV and performance of elite alpine skiers.